2012
DOI: 10.1107/s1600536812002589
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-1-(2,6-Dichloro-3-fluorophenyl)-3-(4-fluorophenyl)prop-2-en-1-one

Abstract: In the title compound, C15H8Cl2F2O, the C=C double bond is in the E configuration. In the cyrstal, C—H⋯O hydrogen bonds connect the mol­ecules into chains along the c axis. A π–π inter­action of 3.628 (1) Å is also observed between two polyhalogenated benzene rings. The dichloro­substituted ring exhibits partial disorder over two sets of sites, with site-occupancy factors of 0.573 (3) and 0.427 (3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In (I) ( Fig. 1), all bond lengths and angles are normal and correspond to those observed in (2E)-1-(2,6-dichloro-3fluorophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (Betz et al, 2012). The fluorine atom is disordered over two positions with site occupancy factors of 0.530 (3) and 0.470 3, respectively.…”
Section: S1 Commentsupporting
confidence: 60%
See 1 more Smart Citation
“…In (I) ( Fig. 1), all bond lengths and angles are normal and correspond to those observed in (2E)-1-(2,6-dichloro-3fluorophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (Betz et al, 2012). The fluorine atom is disordered over two positions with site occupancy factors of 0.530 (3) and 0.470 3, respectively.…”
Section: S1 Commentsupporting
confidence: 60%
“…For the biological activity of chalcones, see: Rajendra Prasad et al (2008); Shivakumar et al (2005); Churkin et al (1982); Herencia et al (1998). For a related structure, see: Betz et al (2012). For the graph-set analysis of hydrogen bonds, see: Etter et al (1990); Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: APEX2 (Bruker, 2010); cell refinement: SAINT (Bruker, 2010); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: ORTEP-3 (Farrugia, 1997) and Mercury (Macrae et al, 2008); software used to prepare material for publication: SHELXL97 and PLATON (Spek, 2009 (Lin et al, 2002), anticancer (Modzelewska et al, 2006) and antifungal agents (Svetaz et al, 2004). The crystal structures of some chalcones such as (2E)-1-(2,6-Dichloro-3-fluorophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (Betz et al, 2012) have been reported in the literature. As part of our ongoing studies on chalcones, the title compound was synthesized and characterized by X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…For related structures, see: Betz et al (2012). For graph-set analysis of hydrogen bonds, see: Etter et al (1990); Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…They are also finding application as organic nonlinear optical materials (NLO) for their SHG conversion efficiency (Sarojini et al, 2006). Crystal structures of some related chalcones, viz., (2E)-1-(2,4-dichlorophenyl)-3-(2-hydroxy-3-methoxyphenyl)prop-2-en-1-one (Yathirajan et al, 2007) and (2E)-1-(2,6-dichloro-3-fluorophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (Betz et al, 2012) have been reported. As part of our ongoing studies on chalcones, the title compound (I), C 16 H 11 C l2 FO 2 , was synthesized and its crystal structure is reported.…”
Section: S1 Commentmentioning
confidence: 99%